Rip currents: A spontaneous heat transfer enhancement mechanism in a wickless heat pipe. (March 2020) - Nguyen, Thao T.T.; Yu, Jiaheng; Wayner, Peter C.; Plawsky, Joel L.; Kundan, Akshay; Chao, David F.; Sicker, Ronald J.
Highlights: An unusual analog of a terrestrial rip current in a wickless heat pipe operating in the ISS. Driven by a pair of counterrotating vortices formed from Marangoni and capillary flows. Experimental data are supported by a numerical model. The current arises spontaneously as the heat input increased. It serves as a natural way of enabling higher evaporation rates. Abstract: The liquid-vapor distribution and its effects on the fluid dynamics and heat transfer occurring within a wickless heat pipe are little understood, especially in a microgravity environment. Such information is vital to the design of thermal management systems for deep space robotic and manned exploration missions, especially if unexpected behaviors arise. We observed an unusual analog of a terrestrial rip current during the operation of a wickless heat pipe on the International Space Station. The current arose spontaneously as the heat input increased, flowing along the flat surfaces of the device toward the heater end, and was driven by a pair of counterrotating vortices that formed from the interaction of opposing surface tension and capillary driven corner flows. The current served as a natural way of increasing the total contact line length within the device and this enabled higher evaporation rates than would have been possible based on the engineered geometry of the device alone. Graphical abstract: Image, graphical abstract